Teodisi Allah Dalam Sastra Hikmat Terhadap Penderitaan Orang Benar - Gernaida Krisna R. Pakpahan (Sekolah Tinggi Teologi Arastamar Bengkulu, 2022)
A righteous person who experiences suffering. Making the idea of ​​theodicy where God's sovereignty reigns over the world and also human history is inseparable, including suffering. The issue of suffering is an integral part of the life experience of individuals and communities. The subject of discussion in this study is how wisdom and suffering are understood by humans from the perspective of OT wisdom literature. The purpose of this study is to understand how God's theodicy in human suffering is related to Wisdom Literature. The research method is descriptive qualitative using literature review and Bible study. The findings of this study are that in the suffering that occurs, God continues to declare goodness to humans, suffering is under the sovereignty of God, and with the concept of theodicy, the problem of human suffering can be answered. God's involvement in human suffering shows God's compassionate attitude. Wisdom is a means of solving the problem of suffering, God is just in allowing suffering to occur. His omnipotence still exists in the midst of suffering, In suffering, there is the involvement of God who provides answers to human questions about suffering.